Delayed coking of South African petroleum heavy residues for the production of anode grade coke and automotive fuels - Clark, John Graham (My University, 2009)
A laboratory scale delayed coking process was used to produce petrol precursors, diesel precursors, methane rich gas, green and calcined coke from five previously untested South African heavy petroleum residues. The ash content of the heavy petroleum residues was found to be detrimental to the microstructure of the green coke and Coefficient of Thermal Expansion (CTE) of the calcined coke. The sulphur content of the calcined cokes produced was found to be in-line with typical global anode grade cokes. De-ashing of the feedstock would be necessary to produce anode grade fillers for the aluminium industry. The local production of anode grade coke would serve to reduce imports and supply the aluminium smelters on the east coast of South Africa. The heavy petroleum residues (also known as heavy fuel oil) are currently used as bunker fuel in the shipping industry and are responsible for substantial air pollution. Delayed coking of these residues could extend the production of petrol and diesel per barrel of imported crude oil and reduce the effect on South Africa’s balance of payments deficit and impact the environment in a beneficial manner with respect to carbon dioxide and sulphur emissions. The research also evaluated the replacement of heavy fuel oil with marine diesel produced by delayed coking of the former. Marine diesel was found to emit less sulphur oxides and have a higher energy density per unit of carbon dioxide emitted. While seawater scrubbing of the heavy fuel oil would be more cost effective in reducing the sulphur oxide emissions, it would not contribute to carbon dioxide reductions. The research created a hypothetical scenario to determine the required value of Clean Development Mechanism credits for a marine diesel replacement, were shipping to be incorporated under the Kyoto Protocol in future
Keywords: Delayed coking Heavy residue Anode coke